2017
DOI: 10.1155/2017/2693681
|View full text |Cite
|
Sign up to set email alerts
|

Dual Kidney Transplantation: A Review of Past and Prospect for Future

Abstract: Kidney transplantation (KT) is one of the treatment options for patients with chronic kidney disease. The number of patients waiting for kidney transplantation is growing day by day. Various strategies have been put in place to expand the donor pool. Extended criteria donors are now accepted more frequently. Increasing number of elderly donors with age > 60 years, history of diabetes or hypertension, and clinical proteinuria are accepted as donor. Dual kidney transplantation (DKT) is also more frequently done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…1 A kidney transplant improves a patient's quality of life and increase life expectancy. The number of patients undergoing this procedure worldwide is increasing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 A kidney transplant improves a patient's quality of life and increase life expectancy. The number of patients undergoing this procedure worldwide is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…The number of patients undergoing this procedure worldwide is increasing. 1 A kidney transplant improves a patient's quality of life and increase life expectancy. However, transplant recipients will depend on immunosuppressive drugs and constant medical monitoring for the rest of their lives.…”
Section: Introductionmentioning
confidence: 99%
“…To maintain self-sufficiency and governance, we have an active research unit that had churned out several review articles on transplantation between 2017 and 2019. is was to enable the team to acquaint themselves with transplant literature and keep abreast with the latest transplant developments. Review articles have been published on aspirin usage in kidney transplants [27], hematological cytopenia in kidney transplants [28], use of fluoroquinolone in BK virus nephropathy [29], cigarette smoking in kidney transplants [30], and dual kidney transplantations [31]. Another recent local-driven study in 2017 showed that lack of donors (71%), lack of awareness of the program (21.2%), and unwillingness to take risks (26.5%) were the main barriers to the progress of the program [32].…”
Section: Phase 4: Implementation and Consolidation Of Transplant Program (2013 To Current)mentioning
confidence: 99%
“…Although some centers in the United Kingdom and internationally use preimplantation histologic evaluation to help identify which kidneys should be implanted as duals (2,8,9), no clinical or histologic parameters have been widely accepted to aid utilization decisions (10)(11)(12)(13)(14)(15)(16). There is also little clinical guidance regarding recipient selection, and many offering policies for kidneys from older donors are based on donor criteria alone (17,18). Additional considerations for dual kidney transplantation include increased technical difficulty and longer time under anesthesia (16,19,20).…”
Section: Introductionmentioning
confidence: 99%